17alpha,20alpha-dihydroxy-4-pregnen-3-one, not its 20beta isomer, is produced from 17alpha-hydroxyprogesterone by spermatozoa of secondary male groupers (Epinephelus tauvina) derived from females implanted with 17alpha-methyltestosterone - Tan, A.M. (2014)
Journal of Experimental Zoology